A derivative-type operator and its application to the solvability of a nonlinear three point boundary value problem - Castillo, René Erlín; Sultan, Babar (CUBO, A Mathematical Journal, 2022)
In this paper we introduce an operator that can be thought as a derivative of variable order, i.e. the order of the derivative is a function. We prove several properties of this operator, for instance, we obtain a generalized Leibniz‘s formula, Rolle and Cauchy‘s mean theorems and a Taylor type polynomial. Moreover, we obtain its inverse operator. Also, with this derivative we analyze the existence of solutions of a nonlinear three-point boundary value problem of “variable order”.